You Lose on Every Gallon... - Hercules Incorporated (1940 Hercules Advertisements, 1940)
Advertisement for D.H.S. Activator, a trademarked name for Ethylene glycol ether manufactured and sold by the Hercules Powder Company to increase the effectiveness and reduce the manufacturing costs of pyrethrum and rotenone insecticides and sprays. This advertisement was published in the June 1940 issue of Soap. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Pyrethrum (Insecticide); Chemical industry; Hercules Incorporated; Corporations; Naval stores; Insecticides; Rotenone; Insecticides--Toxicology; Advertising, Industrial; Naval stores industry